Evaluation and In vitro Cell Line Studies of Phyto-Cosmeceutic Gel Based Hand Wash Formulation Using Camellia sinensis (Green Tea) And Myristica fragrans (Nutmeg) - Kulandhaivel, M (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT A phyto-cosmeceutic gel based hand wash was formulated using Camellia sinensis (Green tea) and Myristica fragrans (Nutmeg), and evaluated by physical parameters like, colour, odour, spreadability, pH and overall appearance of the formulation. Identification of unknown materials, determination of quality, consistency, amount of components and detection of functional groups and characterization of covalent bonding information of the formulation was qualitatively analyzed using Shimadzu FTIR-8400S Fourier Transform Infrared Spectrometer instrument and spectra obtained for each sample was interpreted with a chart for interpreted with a chart for Characteristics IR absorption frequencies of organic functional groups and carbonyl containing functional group. The best selected formulation was subjected to invitro cell line studies using 3T3 cells. The in vitro cell line toxicity and cell viability studies.of the formulation was assessed by MTT assay Thus, overall study showed that gel based hand wash containing mixture of Camellia sinensis (Green tea) and Myristica fragrans (Nutmeg) is rich in phyto-chemicals and safe for utility